Resolusi Konflik dalam Masyarakat Religius Indonesia - Roswantoro, Alim (Religió: Jurnal Studi Agama-agama, 2018)
Indonesia, as the plural nation in religion, has already performed a positive and peaceful life of the religious people who are different in faith and understanding. In general, the life of religious people in Indonesia is lasting well and peacefully. It does not mean that there never be religious conflicts of the different religious people in Indonesia. The conflicts had ever occurred and will probably emerge in the future. The conflicts were often seen as threat, or negativity, of religious life among different-religious people in Indonesia. The writing does not deny that indeed the conflicts are not wanted and have to be overcome. But since the conflicts cannot be avoided from the life of different-religious people of Indonesia, the writing philosophically intend to see and understand the conflicts in a different way. The religious conflicts can be positively seen and understood, that is, as part of communication among different-religious people interacting in public sphere. Conflict-resolution that gives the win-win solution for those who are involved in the conflict has to be principle that should be made to be tradition. Conflict resolution will be successful if the transcendently moral principles, such as mutual respect, mutually avoiding deformation of religion, and mutually giving freedom, are provided for all. [Indonesia sebagai negara yang majemuk dalam agama telah menampilkan wajah hidup umat beragama dari agama-agama yang berbeda yang damai. Secara umum, kehidupan umat beragama di Indonesia berjalan dengan penuh kedamaian. Ini bukan berarti tidak pernah ada konflik keagamaan di Indonesia. Konflik-konflik keagamaan telah pernah terjadi dan mungkin akan muncul kembali di masa depan. Konflik-konflik ini sering dilihat sebagai suatu ancaman atau sisi negatif dari kehidupan religius di Indonesia. Tulisan ini tidak memungkiri bahwa konflik-konflik ini memang tidak diinginkan dan harus diatasi. Namun, karena konflik-konflik ini tidak bisa dihindari dalam kehidupan antar umat beragama yang berbeda, tulisan ini mencoba secara filosofis melihat dan memaknai konflik-konflik ini secara berbeda. Konflik-konflik keagamaan bisa dimaknai secara positif, sebagai bagian dari komunikasi antara umat beragama yang berbeda yang berinteraksi dalam ruang publik. Resolusi konflik yang saling memenangkan masing-masing pihak harus menjadi prinsip yang harus ditradisikan. Resolusi konflik akan sukses, jika prinsip-prinsip moral transenden, seperti saling menghargai, saling menghindari deformasi agama, dan saling memberi ruang kebebasan, diberikan untuk semuanya.]